Metabolic Response of Visceral White Adipose Tissue of Obese Mice Exposed for 5 Days to Human Room Temperature Compared to Mouse Thermoneutrality - van der Stelt, Inge; Hoevenaars, Femke; Široká, Jitka; de Ronde, Lidwien; Friedecký, David; Keijer, Jaap; van Schothorst, Evert (Frontiers in Physiology, 2017)
Housing of laboratory mice at room temperature (22°C) might be considered a constant cold stress, which induces a thermogenic program in brown adipose tissue (BAT). However, the early adaptive response of white adipose tissue (WAT), the fat storage organ of the body, to a change from thermoneutrality to room temperature is not known. This was investigated here for various WAT depots, focusing on epididymal WAT (eWAT), widely used as reference depot. Male adult diet-induced obese (DIO) C57BL/6JOlaHsd mice housed at thermoneutrality (29°C), were for 5 days either switched to room temperature (22°C) or remained at thermoneutrality. Energy metabolism was continuously measured using indirect calorimetry. At the end of the study, serum metabolomics and WAT transcriptomics were performed. We confirmed activation of the thermogenic program in 22°C housed mice. Body weight and total fat mass were reduced. Whole body energy expenditure (EE) was increased, with a higher fatty acid to carbohydrate oxidation ratio and increased serum acylcarnitine levels, while energy intake was not significantly different between the two groups. Transcriptome analysis of eWAT identified tissue remodeling and inflammation as the most affected processes. Expression of pro-inflammatory M1 macrophage-related genes, and M1 over M2 macrophage ratio were decreased, which might be linked to an increased insulin sensitivity. Markers of thermogenesis were not altered in eWAT. Decreased expression of tryptophan hydroxylase 2 (Tph2) and cholecystokinin (Cck) might represent altered neuroendocrine signaling. eWAT itself does not show increased fatty acid oxidation. The three measured WATs, epididymal, mesenteric, and retroperitoneal, showed mainly similar responses; reduced inflammation (s100a8), decreased carbohydrate oxidation, and no or small differences in fatty acid oxidation. However, Ucp1 was only expressed and increased in rWAT in 22°C housed mice. Cck expression was decreased in the three WATs, significantly in eWAT and rWAT, in contrast to Tph2, which was decreased in eWAT while not expressed in mWAT and rWAT. Our data show that tissue remodeling, inflammation and neuroendocrine signaling are early responses in WAT to a moderate decrease in environmental temperature.